Deep water [videorecording (DVD)] - Osmond, Louise; Rothwell, Jerry; Swinton, Tilda (Distributed by Genius Entertainment, 2007)
True story of the first solo, non-stop, round-the-world boat race, and the psychological toll it took on its competitors. Sponsored by the Sunday Times of London, the much-ballyhooed event attracted a field of nine, including amateur sailor Donald Crowhurst, who set out to circumnavigate the globe in late 1968. Battling treacherous seas and his own demons, Crowhurst almost immediately comes apart as he faces the isolation of nine months on the high seas.